EVALUASI USER EXPERIENCE DALAM ASPEK USABILITY PADA APLIKASI TUNE MAP - Sugangga, Rayyan; Noviandri, Noviandri; Nathasia, Novi Dian; Irshandy, Daffa Setyo; Rahman, Iradah (JURSIMA, 2025)
Tune Map is a mobile application to empower people with mobility impairments, by providing them with information on city accessibility provided by sighted citizens. Tune Map is an android-based application designed to allow urban residents to report on the condition of their sidewalks, especially the presence of accessibility lanes. The development of the Tunemap Application stopped for 3 years and it is planned that development will resume. This study aims to determine the results of usability testing and the results of User Experience (UX) evaluation of the Tunemap application. The method used is a combination of the Usability Testing method and the WebQual 4.0 method, which allows a more thorough evaluation of application usability based on testing and direct observation and user perception. The results of the usability testing evaluation show things that need to be improved, especially related to the response code “404” and “400” which is fairly large, then from the evaluation based on user feedback shows things that need to be improved, especially related to detailed information and application design and the addition of tracking features or history of routes that have been traveled. The implications of this research can be an improvement or improvement related to the usability of the Tune Map application that can help the mobility of the blind.